A diatom‐inferred record of lake variability during the last 900 years in Lützow–Holm Bay, East Antarctica. (February 2016) - Rudd, Rachel C.; Tyler, Jonathan J.; Tibby, John; Yokoyama, Yusuke; Tavernier, Ines; Verleyen, Elie; Fukui, Manabu; Takano, Yoshinori
ABSTRACT: Decadal–centennial‐scale climate variability in coastal Antarctica remains poorly understood due to the limited number of highly resolved, well‐dated records. We present a 900‐year, decadal‐scale reconstruction based on sedimentary diatoms from Lake Abi in Lützow–Holm Bay, East Antarctica. Hydrological change is inferred from diatom ecological preferences in conjunction with an existing regional training set and implies that lake water specific conductivity, depth and nitrogen availability are the key drivers of diatom assemblage change. Lake Abi underwent a series of subtle environmental changes related to these environmental variables, possibly driven by changes in catchment snow melt and the duration of seasonal ice cover. Ordination is used to trace the major patterns of change in the diatom community, with notable shifts identified between 470 and 400 and at ∼350 cal a BP (where present = CE 1950). The frequency of environmental variability at Lake Abi is broadly consistent with a record of the Interdecadal Pacific Oscillation during the last millennium, but contrasts with the apparent climate stability elsewhere in eastern Antarctica. Further research is required to constrain the limnological and ecological responses of lakes in coastal Antarctica to obtain more rigorous palaeoclimate reconstructions from these sites of immense potential.